Антология выдающихся достижений в науке и технике. Часть 43: Традиционная энергетика. Тепловые электрические станции: состояние и перспективы их развития - Баранов, М.И. (Електротехніка і електромеханіка, 2018)
Приведен краткий научно-аналитический обзор о современном техническом состоянии и ближайших перспективах
развития мировой теплоэнергетики. Рассмотрены основные теплоэнергоустройства, схемы построения и виды тепловых электрических станций (ТЭС). Указаны преимущества и недостатки ТЭС перед другими видами электрических станций, генерирующих тепло и электричество. Приведены основные технические характеристики крупнейших
ТЭС Украины. Обозначены существующие проблемные задачи и возможные пути их решения в области теплоэнергетики Украины. Наведено короткий науково-аналітичний огляд про сучасний технічний стан і найближчі перспективи розвитку світової теплоенергетики. Розглянуті основні теплоенергопристрої, схеми побудови і види теплових електричних станцій (ТЕС). Вказані переваги і недоліки ТЕС перед іншими видами електричних станцій, що генерують тепло і електрику. Приведені основні технічні характеристики найбільших ТЕС України. Позначені існуючі проблемні завдання і
можливі шляхи їх рішення в галузі теплоенергетики України. Purpose. Preparation of brief scientific and technical review
with an analytical analysis about the state, achievements, problems and prospects of development of world thermal power engineering. Methodology. Known scientific methods of collection,
analysis and analytical treatment of the opened scientific and
technical information, present in scientific monographs, journals and internet reports, world level in area of thermal power
engineering. Results. A brief analytical scientific and technical
review is resulted about the present state, achievements, problem tasks and prospects of development of thermal power engineering in the industrially developed countries of the world.
Considerable progress is marked in development and creation
of technical base of modern thermal power engineering including such thermal power devices (TPD) as steam generators,
steam turbines and turbogenerators. Basic TPDs are described,
charts of design and types of the modern thermal power plants
(TPP), producing in the world about 70 % annual production
electric power are presented. From positions of approach of the
systems advantages and lacks of TPPs are described before
other types of electric stations, generating heat and electric
energy in industrial scales. Basic technical descriptions of largest TPPs of Ukraine are resulted, TPDs of powerful power units
of which behave to the morally out-of-date past generation and
characterized a large physical wear. Some topical problem tasks
and possible ways of their decision are indicated in area of
thermal power engineering of Ukraine. In a review an accent is
done on the necessity of development and acceptance of strategic plan of development of thermal power engineering of
Ukraine on the nearest 10 years. A regard is paid to power engineering experts acceleration of rates of introduction in domestic practice of achievements alternative and ecologically clean
power engineering specialists − especially wind energy and sun
energy. Originality. Systematization of the scientific and technical materials touching functioning of such important sector of
world economy as thermal power engineering known from the
sources opened in outer informative space is executed. It is
shown that for normal development and determination of the
nearest prospects for domestic thermal energy the native revision of power politics of Ukraine is needed. Practical value.
Popularization and deepening for students, engineers and technical specialists and research workers of front-rank scientific
and technical knowledge in area of modern thermal energy,
extending their scientific range of interests and further development of scientific and technical progress in society.